Report on The Museum as Archive: Using the Past in the Present and Future: Online Symposium Hosted by the Centre for Research on Colonial Culture, University of Otago, Dunedin, December 2021. Issue 1 (1st July 2022) - Johnson, Miranda
Abstract : In December 2021, the Centre for Research on Colonial Culture at the University of Otago (Dunedin campus) hosted an online symposium, convening Indigenous and non-Indigenous scholars to talk about their work in and with museum and archival collections in the Pacific region. Held over three days, with morning and late afternoon sessions timed to facilitate maximum participation, attendees Zoomed in from Rapa Nui, Munich, New York, Honolulu, Sydney, Melbourne, Auckland, and Wellington. The symposium brought together practitioners, curators, artists, and scholars in a stimulating exchange that will continue into publication.